Acute Effect of Dynamic and Static Stretching Exercises on Targeting Performance in Archery - Turna, Bulent; Bayazit, Burcu; Eryucel, Mehmet Emre; Yildiz, Mustafa; Karademir, Mehmet Bilgin (Progress in Nutrition, 2021)
Study Objectives: This study aimed to investigate the acute effects of dynamic and static stretching exercises on targeting performance in archery. Methods: Thirty intermediate archers participated in the study, 15 females and 15 males. Participants were assigned into three groups randomly which are no stretching (NS), static stretching (SS), and dynamic stretching (DS). 3*10 Arrow shooting test (18 m) were applied to each group on three different days (with minimum 72-hour resting intervals between days) after each different stretching protocols with a random order. SPSS 20 statistical package program was used for statistical analyses and the significance level was set at p